Aluminum Pillared Clay (Al-PILC) for Adsorption of Dyes in Red Fruit Oil - Sholihah Novitasari; Sriatun Sriatun; Taslimah Taslimah (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2021)
Red fruit oil contains carotene, which is dark orange, so it is not very popular. Therefore, it is necessary to reduce the intensity of the color. Yesterday, in this study, the synthesis and characterization of Al-pillared clay (Al-PILC) from light and heavy clay fractions were carried out. The absorption capacity of red fruit carotene dyes was studied. The research stages included preparation, fractionation, activation, pillarization of clay with aluminum, characterization, and adsorption test for carotene dyes on red fruit. Characterization was carried out using X-ray Diffractometer (XRD) and Gas Sorption Analyzer (GSA). The results showed that basal spacing of natural clay, Al pillared heavy fraction-clay, Al pillared light fraction-clay, activated light fraction were 15.08 Å, 15.27 Å, 16.84 Å, and 16, respectively. 22 Å. The GSA results showed that the surface area and pore volume of the Al pillared light fraction-clay of 0.3 was higher than the heavy fraction. The average pore size of Al pillared light fraction-clay and the heavy fraction was found in the mesoporous range of 30-100 Å, and the adsorption isotherm is type IV. Al-pillared light fraction-clay had higher adsorption ability than a heavy fraction and light fraction before pillaring. When the pillaring agent’s concentration was 0.3 M, Al pillared heavy fraction-has absorption capacity is 58.66%, while Al pillared light fraction-clay is 90.4%.